Fluorescence of pyrene-doped polystyrene films from room temperature down to 4 K for wavelength-shifting applications. (20th December 2021) - Benmansour, H.; Ellingwood, E.; Hars, Q.; Di Stefano, P.C.F.; Gallacher, D.; Kuźniak, M.; Pereimak, V.; Anstey, J.; Boulay, M.G.; Cai, B.; Garg, S.; Kemp, A.; et al.
Abstract: In liquid argon-based particle detectors, slow wavelength shifters (WLSs) could be used alongside the common, nanosecond scale, WLS tetraphenyl butadiene (TPB) for background mitigation purposes. At room temperature, pyrene has a moderate fluorescence light yield (LY) and a time constant of the order of hundreds of nanoseconds. In this work, four pyrene-doped polystyrene films with various purities and concentrations were characterized in terms of LY and decay time constants in a range of temperature between 4 K and 300 K under ultraviolet excitation. These films were found to have a LY between 35 and 50% of that of evaporated TPB. All light yields increase when cooling down, while the decays slow down. At room temperature, we observed that pyrene purity is strongly correlated with emission lifetime: highest obtainable purity samples were dominated by decays with emission time constants of ∼ 250–280 ns, and lower purity samples were dominated by an ∼ 80 ns component. One sample was investigated further to better understand the monomer and excimer emissions of pyrene. The excimer-over-monomer intensity ratio decreases when the temperature goes down, with the monomer emission dominating below ∼ 87 K.